AKHLAK DALAM KEHIDUPAN BERKELUARGA - Imam Suraji (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
Having family by marriage is sunnatullah for all the creatures in the world. In human life, family just can be formed by marriage, that is a holy connection between a man and a woman. Religion and moral state that marriage is the only right way to release the sexual desire honorable to get good generation. Because of that, sex without married, live together without married, and having sex with the same gender is a wrong behavior, out of rule, and contrary to compulsary state (fitrah) as human, and it is forbidden by religion. In order to have a happy and harmony family, life in family has to based on love, sincerity, andÂ worship, not because of pressure or just looking for the desire of sex. Because of that, the moralityÂ on the family life has to be understood and done by all members in family (espcially husband and wife), so that, they can create a happy and prosperous family (sakinah mawadah wa rahmah).